Optimizing Packing Material Inventory with ABC Analysis, Forecasting Methods, and Economic Order Quantity: Optimalisasi Persediaan Material Packing dengan Analisis ABC, Metode Peramalan, dan Economic Order Quantity - Marchello Pamolango; Albertus Daru Dewantoro; Lusi Mei Cahya (Universitas Muhammadiyah Sidoarjo, 2026)
The management of packing material inventory in flexible packaging often faces high investment value, inaccurate demand planning, and inefficient ordering, creating a research gap in selecting an integrated optimization method. This study aims to determine material requirements and optimal order quantities to minimize total inventory cost. The methodology integrates ABC Analysis for material classification, forecasting techniques to predict demand, and Economic Order Quantity (EOQ) to determine the most economical order size. The results show that Plywood is classified as category A due to its dominant investment value. Forecasting evaluation using MAPE and Tracking Signal indicates that the 3-period Weighted Moving Average provides the highest accuracy with the lowest error. The EOQ calculation produces an optimal order quantity of 3,304 units for Plywood Multi 0280x0280x09 dia 77, significantly reducing inventory cost. The integration of ABC, forecasting, and EOQ improves inventory efficiency and supports more reliable production planning